GASTRODIPLOMACY: HARNESSING CULINARY TRADITIONS TO BOOST BOROBUDUR'S NATIONAL TOURISM STRATEGIC AREA POLICY - Widyantoro, Sigid; Akhni, Ghaziah Nurika; Noormansyah, Reza; Rahmawati, Yuni; Hidayat, Yudistira Wahyu (Journal of Social Politics and Governance (JSPG), 2025)
Borobudur, a UNESCO World Heritage site in Central Java, Indonesia, plays a crucial role in the nation's tourism by enhancing economic growth and cultural prestige. The Indonesian government has designated Borobudur as part of the National Tourism Strategic Areas (KSPN) to boost tourism while preserving cultural heritage. A key strategy in this initiative is gastrodiplomacy, which uses Indonesia's diverse culinary traditions to attract international tourists, particularly the growing "gastro-tourist" segment. This article explores the potential of local culinary traditions in supporting Borobudur's tourism, highlighting collaborative efforts among various stakeholders to promote sustainable tourism development, economic benefits for local communities, and cultural preservation through gastrodiplomacy. This paper employed a qualitative, interpretive (post-positivist) approach to examine the role of culinary diplomacy in Indonesia's to developing tourism capacity in specified area. The results show; by showcasing its unique culinary offerings and integrating them into a holistic tourism strategy, the Borobudur region can unlock new avenues for growth while providing visitors with authentic cultural immersion.